The Impact of Market Competition, Technological Innovation, Supply Chain Efficiency, and Government Subsidies on Company Productivity and Export Performance in the Manufacturing Industry - Muhammad Zulfan Abdusyakur; Aster Aryati Rakhmasari; Titin Endrawati (The Es Economics and Entrepreneurship, 2025)
This study examines the impact of market competition, technological innovation, supply chain efficiency, and government subsidies on company productivity and export performance in the Indonesian manufacturing industry, with company productivity positioned as a mediating variable. A quantitative research design was employed using data collected from 175 manufacturing firms through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that market competition, technological innovation, supply chain efficiency, and government subsidies each have a positive and significant effect on company productivity and export performance. Furthermore, company productivity is proven to play a significant mediating role in all relationships between the exogenous variables and export performance. These findings indicate that export competitiveness is fundamentally shaped by internal operational efficiency, supported by innovation capability, efficient supply chain management, competitive market pressure, and effective government policy. This study provides both theoretical and practical contributions by integrating internal firm capabilities and external institutional support into a unified framework for understanding export performance in emerging economies.